The physical characteristics of a CO2 seeping fault: The implications of fracture permeability for carbon capture and storage integrity. (June 2017) - Bond, Clare E.; Kremer, Yannick; Johnson, Gareth; Hicks, Nigel; Lister, Robert; Jones, Dave G.; Haszeldine, R. Stuart; Saunders, Ian; Gilfillan, Stuart M.V.; Shipton, Zoe K.; Pearce, Jonathan
Graphical abstract: Highlights: CO2 migration is spatially associated with the Bongwana fault fracture corridor. Cap rock permeability suggests that without fractures it would act as a flow barrier. Elevated CO2 concentration and flux are measured across the fracture corridor. Fracture intensity and orientation variability creates permeability heterogeneity. Seismically unresolvable fracture networks may impact CO2 storage capability. Abstract: To ensure the effective long-term storage of CO2 in candidate geological storage sites, evaluation of potential leakage pathways to the surface should be undertaken. Here we use a series of natural CO2 seeps along a fault in South Africa to assess the controls on CO2 leakage to the surface. Geological mapping and detailed photogrammetry reveals extensive fracturing along the mapped fault trace. Measurements of gas flux and CO2 concentration across the fracture corridor give maximum soil gas measurements of 27% CO2 concentration and a flux of 191 g m −2  d −1 . These measurements along with observations of gas bubbles in streams and travertine cones attest to CO2 migration to the surface. Permeability measurements on the host rock units show that the tillite should act as an impermeable seal to upward CO2 migration. The combined permeability and fracture mapping data indicate that fracture permeability creates the likely pathway for CO2 migration through the low permeability tillite to the surface. Heterogeneity in fracture connectivity and intensity at a range of scales will create local higher permeability pathways along the fracture corridor, although these may seal with time due to fluid-rock interaction. The results have implications for the assessment and choice of geological CO2 storage sites, particularly in the assessment of sub-seismic fracture networks.